GLOBULE LEUCOCYTES AND MAST CELLS IN THE BILIARY SYSTEM OF CATTLE INFECTED WITH CIGANTOCOTYLE EXPLANATUM - J. Alwan, M.; Y.S. Al-Kubaisee, R. (The Iraqi Journal of Veterinary Medicine, 1990)
Globule leucocytes and Mast cells were detected in the epithelial mucosa of the biliary system of system of cattle infected with Gigantocotyle explanatum. The results showed that the cytoplasmic granules of globule leuco- cytes and mast cells were, in large extent, identical in their contents of the acid mucopolysaccharide associated with a highly basic protein.